Effect of etching time and illumination on optical properties of SiNWs elaborated by Metal Assisted Chemical Etching (MACE) for organic photovoltaic applications. (September 2015) - Saidi, H.; Hidouri, T.; Fraj, I.; Saidi, F.; Bouazizi, A.
Highlights: P3HT is deposited directly on Si substrate by spin-coating method. Optical properties of SiNWs and P3HT:SiNWs are investigated. Highest etching time is favorable for a good charge transfer. Abstract: Using Ag-assisted chemical etching technique, vertical silicon nanowires (SiNWs) arrays on n-type (0 0 1) substrates has been prepared with different conditions such as etching time and illumination condition. A photoluminescence measurement at room temperature has shown a decrease of PL intensity when decreasing etching time. These results are attributed to the decrease of SiNWs density and reduction of laser capture surface. The presence of defect states lead to a non-radiative recombination. Indeed, the blue shift observed when using a low etching time is due to the confinement effect. Using a low etching time, illumination condition does not vary SiNWs density. The optimal experimental condition for photovoltaic application is observed after deposition of Poly (3-hexylthiophene-2, 5-diyl) P3HT into the different silicon substrates prepared. An important charges transfer between P3HT and SiNWs is observed for high etching time (120 min under illumination). A blue shift is due to the presence of defects and electric field.